If sharing is everything, then it is nothing: A multidisciplinary survey on basic terms, views and current research topics - Magnus Richter; Rainer Souren (VERLAG proWiWi e.V., 2018)
[Introduction ...] The paper is organized as follows: Chapter 2 depicts the state-of-the-art of sharing research and outlines the practical and scientific relevance of sharing. Furthermore, the contribution of the paper is defined. Chapter 3 describes the participants and the survey design. Chapter 4 presents commonalities and controversies in the participants' feedbacks, including sharing examples, definitions and key statements. Chapter 5 focuses on the definition problem and provides a typology that enables researchers to specify their own sharing paradigm. Chapter 6 summarizes the results and their practical benefits.
urn:nbn:de:gbv:ilm1-2018200182
Keywords: 650; Sharing Economy